Lung cancer exosome protein marker based on flow technology and application of lung cancer exosome protein marker in lung cancer screening - ZHU SHICHENG; PAN DANHUA; ZHU WANYING; YANG YING; ZHANG JING (2023)
The invention provides a lung cancer exosome protein marker based on a flow technology and application of the lung cancer exosome protein marker in lung cancer screening, according to the method, by means of conjoint analysis of exosome protein markers CD151 protein, TTF-1 protein and SFTPB protein, the lung cancer exosome protein marker can be used for screening lung cancer by detecting the proportion of positive exosomes containing CD151, TTF-1 and SFTPB protein in human plasma. In-vitro diagnosis and risk screening of lung cancer are carried out on subjects according to different ratios of healthy groups and lung cancer high-risk groups. The exosome protein combination can eliminate interference of exosomes from other tissues or diseases, the detection difficulty is reduced, and the problems that an existing detection method is low in sensitivity, poor in tissue specificity, large in detection difficulty and the like are solved. Corresponding protein targets are labeled by different fluorescence, then dete